'A damn sight more sensitivity': gender and parent-school engagement during post-separation family transitions. Issue 1 (2nd January 2022) - Saltmarsh, Sue; Tualaulelei, Eseta; Ayre, Kay
ABSTRACT: This paper considers the importance parents place on engaging with children's schools following the dissolution of parental intimate partner relationships. These periods of family transition typically involve many changes to everyday life, and can be complicated by tensions, disputes and competing agendas between parties. During such times, school staff may be unaware of family circumstances, uncomfortable about being privy to what many consider private matters, or unsure of their responsibilities based on the information available to them. For parents, however, the link between home and school can be a critical aspect of maintaining community connections and supporting children's learning and wellbeing during a time of personal and family upheaval. Here we draw on in-depth interviews with four Australian parents, whose experiences highlight how gendered norms and assumptions that underpin everyday school activities and practices can create exclusions and additional demands for families in need of sensitivity, safety and support.